AKIBAT HUKUM TERHADAP PENGUNGKAPAN RAHASIA DAGANG OLEH BARISTA COFFEE SHOP BERDASARKAN IUS CONSTITUTUM - I Nyoman Ari Franthika Laksana Putra Parwata; I Nyoman Suandika; Kadek Dedy Suryana (Yayasan Nusantara Hasana Berdikari, 2025)
Amidst the growth of coffee shops, this poses a challenge for coffee shop entrepreneurs themselves. It is not uncommon for many baristas to move from one coffee shop to another, leaving their old coffee shop for a new one due to higher pay, a more comfortable work environment, or other reasons. However, when a barista moves from an old coffee shop to a new one, it does not mean that they can use the trade secrets of the coffee shop they left to benefit the new coffee shop where they now work. The research question in this study is: How is legal protection for trade secrets based on Law Number 30 of 2000 implemented in coffee shops? What are the challenges and efforts made regarding legal protection for trade secrets based on Law Number 30 of 2000 in coffee shops? The objectives of this study are to explain the legal protection of trade secrets under Law No. 30 of 2000 in coffee shops and to explain the obstacles and efforts made regarding the legal protection of trade secrets under Law No. 30 of 2000 in coffee shops. The type of research is normative legal research. Furthermore, the data was collected using qualitative analysis. The results of this study show that if the barista misuses trade secrets by disclosing confidential information to third parties, such as coffee bean ingredients, recipes, compositions, and methods of making coffee drinks, which are done intentionally without the knowledge of the coffee shop owner while still working at the coffee shop.